2019
DOI: 10.20524/aog.2019.0395
|View full text |Cite
|
Sign up to set email alerts
|

Safety and clinical outcomes of endoscopic ultrasound-guided gallbladder drainage with lumen-apposing metal stents in patients with dwell time over one year

Abstract: Background: Endoscopic ultrasound-guided gallbladder drainage (EUS-GBD) has proved effective in patients with cholecystitis at high surgical risk. The long-term risks of gallstone-related disease and stent-related adverse events are unknown. Methods: We performed a retrospective evaluation of a case series including subjects who underwent EUS-GBD using lumen-apposing metal stents (LAMS). Patients were identified from a prospective LAMS registry at a single tertiary cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
1
12
1
1
Order By: Relevance
“…Regarding migrations, we found a rate of 14% in our series, higher than other published series [4,5]. However, this is justified by most migrations occurring late in our series with a median This article is protected by copyright.…”
Section: Accepted Manuscriptcontrasting
confidence: 73%
See 1 more Smart Citation
“…Regarding migrations, we found a rate of 14% in our series, higher than other published series [4,5]. However, this is justified by most migrations occurring late in our series with a median This article is protected by copyright.…”
Section: Accepted Manuscriptcontrasting
confidence: 73%
“…Some authors advocate removing the LAMS weeks after EUS-GBD to avoid long-term AEs associated with LAMS [4], similar to studies using LAMS in pancreatic fluid collection. In contrast, other authors have suggested indwelling LAMS, given the fragility of these patients [5].…”
Section: E1063mentioning
confidence: 84%
“…The most common adverse events reported after endoscopic intervention are stent malfunction, bleeding, and acute pancreatitis (with transpapillary stent placement). In addition to short-term adverse events, there are data reporting the long-term safety of EUS-GBD with LAMS in patients who are 2-3 years out from initial intervention suggesting that this technique can be used as a more permanent solution (11,12). When considering length of hospitalization, data suggest that the 2 endoscopic techniques lead to shorter hospital lengths of stay when compared with PTGBD.…”
Section: Patient and Technique Selectionmentioning
confidence: 99%
“…Recently, Yuste et al 28 have performed a retrospective evaluation of a case series including subjects who underwent EUS-GBD using LAMS, in order to evaluate the safety and clinical outcomes after at least 1 year of follow up. In this study, no LAMS-related AE were identified after the first 12 months of follow up, and only 4.5% of patients required re-admission for the gallstone-related disease.…”
Section: Long-term Outcomes Of Eus-gbdmentioning
confidence: 99%